Analysis of the Influence of Social Media on Marketing Information Systems in the Digital Business World - Khairul Akmal (STMIK Indonesia Banda Aceh, 2023)
This research aims to analyze the impact of social media use on marketing information systems in the context of digital business. The research method used was an online survey of a series of companies active in digital business, with a focus on the use and integration of social media in their marketing strategies. Data was collected through questionnaires distributed to marketing managers and analysis was carried out using descriptive statistical techniques. The research results show that social media has a significant influence on marketing information systems, with increased interaction between consumers and brands and efficiency in conveying marketing messages. Additionally, it was found that proper integration between social media and marketing information systems can increase the effectiveness of digital marketing strategies. In conclusion, the use of social media in the context of digital business has become a crucial element in strengthening marketing information systems, providing a vital platform for consumer interaction, and improving overall marketing performance. The practical implications of this research emphasize the importance for companies to understand and utilize social media effectively in optimizing their marketing information systems in the digital era.